2018
DOI: 10.37358/mp.18.1.4956
|View full text |Cite
|
Sign up to set email alerts
|

Railway Vehicle Pneumatic Rubber Suspension Modelling and Analysis

Abstract: The pneumatic elastic elements are widely used in the secondary suspension of modern railway vehicles due to their important advantages compared to the conventional ones. In the present paper, the modelling and analysis of the pneumatic suspension is approached, taking into account the main elements, pneumatic enclosures and rubber elements. The analysis performed investigates the influence of relevant parameters on suspension stiffness and on its dynamic response.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
5
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 15 publications
(5 citation statements)
references
References 5 publications
0
5
0
Order By: Relevance
“…In paper [6] a method of determining the equivalent rigidity of an air spring was proposed, which additionally takes into account the rigidity of the emergency spring:…”
Section: Analysis Of Literary References and Problem Statementmentioning
confidence: 99%
“…In paper [6] a method of determining the equivalent rigidity of an air spring was proposed, which additionally takes into account the rigidity of the emergency spring:…”
Section: Analysis Of Literary References and Problem Statementmentioning
confidence: 99%
“…In the literature [24,42], the heat exchange in air springs is evaluated isothermally and adiabatically to defne their physical behavior. Similarly, Spiroiu reported that when the frequencies are above 0.3 Hz, the process can be termed adiabatic, and frequencies ranging from 0.1 to 0.3 Hz are deemed polytropic, while frequencies below 0.1 Hz are isothermal processes [43]. Tis claim was however challenged by Pintado et al whose experimental research fndings revealed otherwise.…”
Section: Types Of Pneumatic Suspension Systemmentioning
confidence: 99%
“…However, it is applied in many vehicle suspension simulations. For instance, the efects of an auxiliary chamber and air pipeline parameters on a pneumatic suspension system performance are modeled using the vampire model [55], and the infuence of parameter estimation of the airbag, rubber spring, and auxiliary reservoir on the suspension stifness was also investigated [43]. Among the various models under this category, the Nishimura linear model and Simpack FE83 model are deemed to be more accurate in depicting the actual behavior of an air spring, and this is because both models factor in the viscous damping, including modeling the efect of air spring orifce and connecting pipelines.…”
Section: Types Of Pneumatic Suspension Systemmentioning
confidence: 99%
“…Several scholars have studied the equivalent mechanical models with the combination of spring and damping terms. 37 Mazzola and Berg 8 concluded six equivalent mechanical models and compared them with the experiment. Zhu et al 9 improved the Berg model to get a four-parameter fractional derivative model which can reflect the hysteresis and frequency-dependency of air springs.…”
Section: Introductionmentioning
confidence: 99%